2021
DOI: 10.1097/j.pain.0000000000002543
|View full text |Cite|
|
Sign up to set email alerts
|

Antibody-induced pain-like behavior and bone erosion: links to subclinical inflammation, osteoclast activity, and acid-sensing ion channel 3–dependent sensitization

Abstract: Several bone conditions, eg, bone cancer, osteoporosis, and rheumatoid arthritis (RA), are associated with a risk of developing persistent pain. Increased osteoclast activity is often the hallmark of these bony pathologies and not only leads to bone remodeling but is also a source of pronociceptive factors that sensitize the bone-innervating nociceptors. Although historically bone loss in RA has been believed to be a consequence of inflammation, both bone erosion and pain can occur years before the symptom ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 107 publications
1
21
0
Order By: Relevance
“…From numerous reports, it has been clarified that the level and metabolism process of LPC in the body fluid or tissues of animals or humans are elevated in various chronic pain states, such as chronic inflammatory pain [ 81 ], chronic joint pain [ 82 , 83 ] neuropathic pain [ 29 , 39 , 84 ], fibromyalgia [ 16 ], and multisite musculoskeletal pain [ 38 ] ( Table 2 ). In this section, we summarize these LPC-induced responses and cellular mechanisms in detail.…”
Section: Lysophosphatidylcholine and Chronic Pain Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…From numerous reports, it has been clarified that the level and metabolism process of LPC in the body fluid or tissues of animals or humans are elevated in various chronic pain states, such as chronic inflammatory pain [ 81 ], chronic joint pain [ 82 , 83 ] neuropathic pain [ 29 , 39 , 84 ], fibromyalgia [ 16 ], and multisite musculoskeletal pain [ 38 ] ( Table 2 ). In this section, we summarize these LPC-induced responses and cellular mechanisms in detail.…”
Section: Lysophosphatidylcholine and Chronic Pain Diseasesmentioning
confidence: 99%
“…Chronic joint pain is the main reason for patients to seek medical treatment for chronic pain; it seriously affects the quality of life of patients, resulting in disability and psychological distress [ 82 ]. Rheumatoid arthritis (RA) and osteoarthritis (OA) are associated with a risk of developing persistent chronic joint pain [ 83 ]. Florian Jacquot et al demonstrated that LPC correlated with pain outcomes in a cohort of chronic joint pain patients.…”
Section: Lysophosphatidylcholine and Chronic Pain Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify potential drivers of nociplastic pain in FM we used a passive transfer mouse model to investigate a role for pathogenic, pain-driving IgG antibodies (9). IgG can induce pain independent of overt inflammation or nerve damage (1012) and a role for antibodies has been identified in other nociplastic pain conditions (1315). We found that transferring FM IgG into mice induces pain-like behaviour, nociceptor sensitization and hyperactivity, and decreased intraepidermal nerve fiber density (9), all of which are characteristics of FM (4,5).…”
Section: Introductionmentioning
confidence: 99%